Vaccines against Meningococcal Diseases - Pizza, Mariagrazia (Microorganisms, 2020)
Neisseria meningitidis is the main cause of meningitis and sepsis, potentially life-threatening conditions. Thanks to advancements in vaccine development, vaccines are now available for five out of six meningococcal disease-causing serogroups (A, B, C, W, and Y). Vaccination programs with monovalent meningococcal serogroup C (MenC) conjugate vaccines in Europe have successfully decreased MenC disease and carriage. The use of a monovalent MenA conjugate vaccine in the African meningitis belt has led to a near elimination of MenA disease. Due to the emergence of non-vaccine serogroups, recommendations have gradually shifted, in many countries, from monovalent conjugate vaccines to quadrivalent MenACWY conjugate vaccines to provide broader protection. Recent real-world effectiveness of broad-coverage, protein-based MenB vaccines has been reassuring. Vaccines are also used to control meningococcal outbreaks. Despite major improvements, meningococcal disease remains a global public health concern. Further research into changing epidemiology is needed. Ongoing efforts are being made to develop next-generation, pentavalent vaccines including a MenACWYX conjugate vaccine and a MenACWY conjugate vaccine combined with MenB, which are expected to contribute to the global control of meningitis.